Analysis Of The Potential Of Natural Sterol Compounds From Tin (Ficus carica) Leaves as Anti-Hypercholesterolemia with In Silico Tests - Taihuttu, Monalisa Pertiwi Jeriska; Manurung, Brian Saputra; Simal, Rufiati; Watung, Fernando A. (Indonesian Biodiversity Journal, 2025)
This study aims to determine the potential of natural sterol compounds from Tin (Ficus carica) leaves as anticholesterolemic using in silico test. This study employed an in silico approach using molecular docking methods to evaluate the potential of sterol compounds as anti-hypercholesterolemic agents, in comparison to other references compounds. Data processing and interpretation were conducted using molecular databases for both ligands and target proteins. The analysis utilized several computational tools, including PyRx 0.8, PyMOL, LigPlus, and Discovery Studio 2016 Client. The compounds used in this research  were sterol, fluvastatin and simvastatin (as control), with HMG CoA reductase as the target protein. The results showed that the highest binding affinity value was fluvastatin which is -8.3 kcal/mol. Sterol compounds are compounds with lower binding affinity which is -7.7 kcal/mol. From the visualization results, it is known that the binding distance between sterol compounds with target proteins (HMG CoA reductase) is between 2.69 to 5.49 Å, and the binding distance between simvastatin compounds with target proteins (HMG CoA reductase) is between 2.76 to 5.36 Å, and the binding distance between fluvastatin compounds with target proteins (HMG CoA reductase) is between 1.95 to 5.26 Armstrong. While based on the comparison of the binding side of strerol, simvastatin and fluvastatin, it is known that the three compounds have the same site because they bind to the same amino acid residues, namely ARG (B: 515), TYR (A: 533), TYR (B: 533), TYR (B: 517), PRO (A: 511). The results of this research indicate that the natural sterol compounds found in Tin (Ficus carica) leaves have potential as anti-hypercholesterolemic agents, based on reverse docking analysis. These sterol compounds bind to the same active site as the control drugs, simvastatin and fluvastatin, and exhibit comparable binding affinity values